Elucidation of Confined Copper Nanospheres within Self-Assembled Curcumin-Cysteine and Their Electrocatalytic Application. Issue 12 (1st January 2019) - Kumar, M. Kaleesh; Jha, Niki S.; Yadav, Ramesh; Jha, Shailendra K.
Abstract : By introducing Cu into the self-assembled curcumin-cysteine on gold electrode, the surface reactivity has been tuned by potentiodynamic electrodeposition approach. The synthesis of curcumin-cysteine has been carried out by modified Fischer esterification method and confirmed by FT-IR, 1 H, and 13 C NMR spectroscopy, respectively. The self-assembly of curcumin-cysteine on gold electrode has been confirmed by electrochemical techniques like, cyclic voltammetry and electrochemical impedance spectroscopy (EIS). The surface confinement of modular copper nanospheres and its bi-dentate complexation with the diketo moiety of self-assembled curcumin-cysteine is enhancing the catalytic activity. Further, as-constructed electrochemical platform has been exploited for electrocatalytic application like: electroreduction of p -nitrophenol and also tested for real world sample analysis. The fabricated sensor has shown an enhanced sensitivity (i.e, 153.08 μAμM −1 cm −2 ) and low level of detection (i.e, 57 nM) of p -nitrophenol as well as good selectivity in the presence of interfering species. The present investigation is providing an ideal approach for resource limited settings to construct an economically viable sensor and molecular electronic devices.